Genome-Wide Mining of Wheat DUF966 Gene Family Provides New Insights Into Salt Stress Responses - Zhou, Xiaoyi; Zhu, Xiaoguo; Shao, Wenna; Song, Jinghan; Jiang, Wenqiang; He, Yiqin; Yin, Junliang; Ma, Dongfang; Qiao, Yongli (Frontiers in Plant Science, 2020)
Domain of unknown function (DUF) proteins constitute a great deal of gene families that encode functionally uncharacterized proteins in eukaryotes. DUF966 gene family is found in monocotyledons and mosses. However, little is known of their functions in wheat. In this study, we identified DUF966 gene family in wheat by in silico analysis. Consequently, 28 DUF966 proteins were found in wheat reference genome, which can be phylogenetically divided into two sub-groups (Group I and II). A highly conserved DUF966 domain and motif distribution existed in each group, implying their functional conservation. Analysis of expression profiling data showed that some TaDUF966 genes responded to salt-stress. We next confirmed the role of TaDUF966-9B using virus induced gene silencing (VIGS) assays in wheat seedling. The results revealed that, comparing to control, the TaDUF966-9B knock-down plants exhibited severe curling leaves at 10 days after inoculation under salt treatment conditions, indicating that TaDUF966 potentially plays a vital role in conferring salt tolerance in wheat. Taken together, these results expand our knowledge of the evolution of the DUF966 gene family in wheat, and promote their potential application in wheat genetic improvement.